Seismic performance between unrepaired and repaired of tunnel form building under lateral cyclic loading / Shamilah Anudai@Anuar - Anudai@Anuar, Shamilah (Institute of Graduate Studies, UiTM, 2017)
A total numbers three units of one-third scale 3-storey tunnel form building (TFB) were designed using BS8110, constructed, tested under in-plane and out-of-plane lateral cyclic loading in the heavy structural laboratory. Two numbers of single units TFB were repaired using steel angle, steel plate and CFRP fabric and retested under in-plane and out-ofplane lateral cyclic loading. Another double unit TFB also repaired using additional shear wall, steel angle and CFRP fabric and retested under in-plane lateral cyclic loading only. The visual observation of damages, lateral strength capacity, stiffness, ductility and equivalent viscous damping were determined for all the unrepaired and repaired specimens. Based on the experimental results, the repaired of single unit TFB using steel angle, steel plate and CFRP fabric has higher value of lateral strength capacity, ductility and equivalent viscous damping than unrepaired single unit TFB. Likewise, the repaired double unit TFB using additional shear wall, steel angle and CFRP fabric also has higher value of lateral strength capacity, stiffness, ductility and equivalent viscous damping than unrepaired double unit. It was found that the repaired double unit TFB is the best method of repair and retrofit technique for this research work…